Rapid and facile chemical actinometric protocol for photo-microfluidic systems using azobenzene and NMR spectroscopy. Issue 47 (7th June 2017) - El Achi, Nassim; Bakkour, Youssef; Chausset-Boissarie, Laëtitia; Penhoat, Maël; Rolando, Christian
Abstract : A new protocol for determining the photon flux inside a photomicroreactor is described using ( E )-azobenzene and NMR spectroscopy which does not require the determination of the quantum yield of the unstable Z isomer. Abstract : In this study, the photon flux inside a photomicroreactor was determined using chemical actinometry via the photoisomerization of azobenzene at 365 nm. For this purpose, a differential equation, in which the only external data are the tabulated absorption coefficient and the quantum yield of the E isomer, was derived enabling the use of concentrated solutions of azobenzene needed for simple NMR spectroscopy analysis. The developed protocol is shown to be efficient when working using different concentrations, light intensities and solvents.